PENDIDIKAN POLITIK OLEH PARTAI NASIONAL DEMOKRAT (NASDEM) KOTA PEKANBARU TAHUN 2015-2016 - Ichwan Nur Fadillah; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In act No. 2 of 2011 on political parties mention one of the functions of political parties is as a means of political education for members dan the public to become Indonesian citizens who are aware of their rights and obligations in society, nation and state. This means that all political parties in Indonesia have an obligation to educate the whole society, with materials that have been provided for in Act No. 2 of 2011 on political parties.This study aimed to describe the role of DPD NasDem Party in providing political education to the people in Pekanbaru city, and the factors inhibiting for political education. The method used is descriptive qualitative, data collection was done by interview and documentation. Sources of data obtained from DPD NasDem Party Pekanbaru, and futhermore, the data obtained from study site will be processed and analyzed further by way of outlining the facts which has been found from the study site.The results showed that DPD NasDem Party Pekanbaru had done political education to the general public, however, given the political education is not maximized. The several things that affect the political education so that political education was to be not optimal. The study recommends the need for change in providing political education to the people, good change of form of communication, material, and methods of implementation, in order to achieve the real goal of providing political education to the community.Keyword : political parties, Partai Nasional Demokrat (NasDem), and Political education